Increased Von Willebrand factor, decreased ADAMTS13 and thrombocytopenia in melioidosis - Birnie, Emma; Koh, Gavin C. K. W.; Löwenberg, Ester C.; Meijers, Joost C. M.; Maude, Rapeephan R.; Day, Nicholas P. J.; Peacock, Sharon J.; Poll, Tom van der; Wiersinga, W. Joost (PLoS neglected tropical diseases, 2017)
Melioidosis, caused by bioterror treat agent Burkholderia pseudomallei, is an important cause of community-acquired Gram-negative sepsis in Southeast Asia and Northern Australia. New insights into the pathogenesis of melioidosis may help improve treatment and decrease mortality rates from this dreadful disease. We hypothesized that changes in Von Willebrand factor (VWF) function should occur in melioidosis, based on the presence of endothelial stimulation by endotoxin, pro-inflammatory cytokines and thrombin in melioidosis, and investigated whether this impacted on outcome. We recruited 52 controls and 34 culture-confirmed melioidosis patients at Sappasithiprasong Hospital in Ubon Ratchathani, Thailand. All subjects were diabetic. Platelet counts in melioidosis patients were lower compared to controls (p = 0.0001) and correlated with mortality (p = 0.02). VWF antigen levels were higher in patients (geometric mean, 478 U/dl) compared to controls (166 U/dL, p<0.0001). The high levels of VWF in melioidosis appeared to be due to increased endothelial stimulation (VWF propeptide levels were elevated, p<0.0001) and reduced clearance (ADAMTS13 reduction, p<0.0001). However, VWF antigen levels did not correlate with platelet counts implying that thrombocytopenia in acute melioidosis has an alternative cause. Thrombocytopenia is a key feature of melioidosis and is correlated with mortality. Additionally, excess VWF and ADAMTS13 deficiency are features of acute melioidosis, but are not the primary drivers of thrombocytopenia in melioidosis. Further studies on the role of thrombocytopenia in B. pseudomallei infection are needed.